Using the secafé technique in seeds of different cultivars - Araujo, Alisson Vinicius de; Araujo, Eduardo Fontes; Abud, Haynna Fernandes; Araujo, Izabel Cristina Vaz Ferreira de (Coffee Science - ISSN 1984-3909, 2016)
The withdrawal of parchment accelerates the emergence of coffee seedlings. When performed manually, it is impractical for large volumes of seed. The SECAFÉ technique promotes parchment degradation by the action of sodium hypochlorite. The objective was to verify the effects of cultivars in the emergence and seedling production, after applying the SECAFÉ technique. The experiment was carried out in a factorial 10 x 3; 10 varieties of coffee and three conditions of parchment seed (intact, removed by hand and removed with sodium hypochlorite) in a completely randomized design with four replicates. For the purposes of SECAFÉ technique, the seeds, although with parchment, were immersed in a solution of NaClO (4% active chlorine) at a ratio of 50 ml for every 100 seeds at 25 ° C for 6 h. We evaluated the speed index and the percentage of emergence, stem diameter, the number of fully expanded leaves and the height and dry matter of the aerial part of seedlings, 150 days after sowing. The results were submitted to analysis of variance and means were compared by Tukey test (p <0.05). In general, for all traits, the application of SECAFÉ technique provides superior results for most cultivars, compared to other treatments. The application of this technique, which is low cost, easy and fast implementation, is effective in parchment degradation of seeds of different cultivars. This enables the acceleration of seedling emergence and seedling.